The relationship between humeral torsion and arm injury in baseball players: A systematic review and meta-analysis - Helmkamp, J. K.; Bullock, G. S.; Rao, A.; Shanley, E.; Thigpen, C.; Garrigues, G. E. (Sports Health: A Multidisciplinary Approach, 2020)
Context: Humeral torsion (HT) has been linked to various injuries and benefits. However, the exact interplay between HT, shoulder range of motion (ROM), competition level differences, and injury risk is unclear.